Penguatan Kesejahteraan Masyarakat melalui Pelatihan Ternak, Manajemen Keuangan, dan Koperasi Syariah - Arifin, Samsul; Zaki, Irham; Ryandono, Muhammad Nafik Hadi; Zulaikha, Siti; Hendratmi, Achsania; Rani, Lina Nugraha; Bayuny, Ahmad Fadlur Rahman; Wijayanti, Ida (Jurnal Ilmiah Pengabdian dan Inovasi, 2024)
This community service program was conducted to enhance the welfare of the residents in Sumber Sawit Village, Sidorejo District, Magetan Regency, through training in livestock management, financial literacy, and the development of Islamic cooperatives. The village faced key challenges, including limited technical knowledge in livestock management, restricted access to capital, and low financial literacy. The Participatory Action Research (PAR) approach was employed to actively involve the community in problem identification, training sessions, and program evaluation. The results indicated significant improvements in the community’s capabilities, including more efficient livestock management, enhanced financial literacy, and the utilization of Islamic cooperatives as an alternative community-based financing option. This program received high appreciation from the community and village leaders for its success in creating an inclusive, equitable, and sustainable local economic ecosystem. These findings highlight the effectiveness of a holistic approach that integrates technical training, financial literacy, and cooperative development as a model for empowering communities to support sustainable local economic development.